Tribological Study of Nanoparticles Enriched Bio-based Lubricants for Piston Ring-Cylinder Interaction - Gulzar, Mubashir; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis investigates the tribological viability of bio-based base stock to which different nanoparticles were incorporated for engine piston-ring-cylinder-liner interaction. It determines experimentally the effects of lubricating oil conditions (new and engine-aged) on the friction and wear of the materials used for piston rings and cylinder liners. The specific base stock examined was a trimethylolpropane (TMP) ester derived from palm oil, and the nanoparticles were used as additives to obtain tribologically enhanced bio-based lubricants. The overall analysis of the results demonstrated the potential of nanoparticles to improve the tribological behavior of bio-based base stock for piston-ring-cylinder-liner interaction.
Introduction -- Literature Review -- Research Methodology -- Results and Discussion -- Conclusions and Recommendations.
Keywords: Engines; Coatings; Tribology; Corrosion and anti-corrosives.; Nanoscience; Engine Technology; Coatings; Tribology; Corrosion; Nanophysics